2021
DOI: 10.1016/j.jcot.2021.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of central chondrosarcoma of bone. One UK-based orthopaedic oncology unit’s experience of 33 years referrals

Abstract: Aim: To ascertain the changing incidence over time of the three commonest primary sarcomas of bone. Data obtained with particular reference to central chondrosarcoma from the annual referral rate to a large UK-based specialist orthopaedic oncology unit. To discuss how the "barnyard pen" analogy of cancers previously applied to certain commoner cancers can also be applicable to central chondrosarcoma (CS) of bone. Materials and methods: A retrospective review was conducted of a computerised database identifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…2-4,9,19 This is because complications and the negative side-effects of surgery make it relevant to evaluate whether active surveillance through wait-and-scan is safe. 13,14,19-22…”
Section: Discussionmentioning
confidence: 99%
“…2-4,9,19 This is because complications and the negative side-effects of surgery make it relevant to evaluate whether active surveillance through wait-and-scan is safe. 13,14,19-22…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the WHO classification from chondrosarcoma grade 1 of the long bones to atypical cartilaginous tumor (ACT), together with the recent insight of low transformation risk of ACTs (<1%), has resulted in a more conservative treatment approach of ACTs in literature [1,2,6,7]. Many authors have questioned if the negative side effects of surgical treatment outweigh the potential benefits and; therefore, proposed active surveillance [6,8,10,12,[14][15][16]. To support development of evidence-based guidelines for active surveillance, we studied the natural course of enchondroma and ACTs in the long bones.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a rise in incidence of chondrosarcoma over the last decades, which is mainly caused by ACTs and might be explained by a simultaneous increase of MRI usage, resulting in more incidental findings [6,7]. Similarly, the incidence of enchondroma increased over the last decades [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations